IMPLEMENTASI METODE HOME VISIT PADA PEMBELAJARAN PAI DI MTs NEGERI 5 MALANG KECAMATAN DONOMULYO KABUPATEN MALANG - Alvi Husnuzzakiya; Abdul Jalil; Adi Sudrajat (VICRATINA, 2021)
The implementation of the home visit method in Islamic education learning is a new challenge experienced by teachers and students at MTs Negeri 5 Malang. The focus of this research is to discuss the planning, implementation and supporting and inhibiting factors of the home visit method in learning Islamic education. To achieve this goal, the researcher uses a qualitative approach based on phenomenology by using case study research. Researchers found the results of this study include planning the implementation of one-sheet learning, face-to-face and home visits. The implementation of this research includes indicators of teacher introduction to student life, ensuring a meeting schedule between teachers and parents, preparing teaching materials for students, and evaluation materials during home visit learning. While the supporting factor for home visit learning is the high willingness of students to learn even in a pandemic. For the inhibiting factor is the selection of time that is  still not appropriate and the geographical conditions of the students' homes. Kata Kunci: Implementation, Home Visit, Islamic Education